ELTROMBOPAG ASSOCIATED CEREBRAL VENOUS SINUS THROMBOSIS IN A CHILD WITH IMMUNE THROMBOCYTOPENIA PURPURA: A CASE REPORT - Evita Ammu Thomas; Heeba Susanna Reji; Aswathy Menon (World Journal of Biology Pharmacy and Health Sciences, 2026)
Immune thrombocytopenia purpura (ITP) is initially treated with steroids, but TPO-RAs such as Eltrombopag are used for chronic cases. Although thromboembolic events associated with Eltrombopag have been reported in approximately 2–6% of treated patients, cerebral venous thrombosis is an uncommon and potentially serious manifestation. This case reports a 10-year-old female with ITP who developed dural sinus thrombosis on Eltrombopag initiation. Withdrawal of the drug and initiation of anticoagulants showed improvements highlighting the need for regular monitoring of platelet counts. Based on the Naranjo Adverse Drug Reaction Probability Scale and the WHO–UMC Causality Assessment Scale, the causality of the adverse drug reaction was classified as probable (Score=7).